The state of the macular zone of the retina in children with pseudophakia after surgical treatment of unilateral congenital cataracts - L. A. Katargina; T. B. Kruglova; N. S. Egiyan; O. B. Trifonova (Российский офтальмологический журнал)
Purpose: to assess the morphometric state of the macula in children with pseudophakia after the removal of unilateral congenital cataract (UCC). Material and methods. 17 children with pseudophakia aged 4.5 to 9 years were examined after UCC extraction removal In addition to traditional techniques, comprehensive ophthalmic examination included optical coherence tomography on Spectralis HRA + OCT (Heidelberg Engineering). OCT data were used to individually analyze the morphometric parameters of the central zone of the eye fundus, including the minimum thickness of the retina in the fovea, the maximum thickness of the retina in parafovea, the thickness of the retina 3.0 mm from the foveola, the width (diameter) of the fovea, and the thickness of the choroid in the subfoveolar area. The parameters were compared with those of the fellow eyes (considered as healthy). Phakoaspiration of UCC with IOL implantation was performed at the age from 5 months to 6.2 years. The optical power of the IOL was determined by the standard formula SRKII. Results. Children with pseudophakia who underwent UCC extraction revealed divergences in morphometric parameters of OCT and its visual image, which testifies to a severe violation inthe differentiation of the macula.The observed correlation between the anatomical and morphological status of the macula as identified from OCT data and the functional status as determined from visual acuity measurements makes it possible to use OCT data in the assessment and prediction of visual functions in children with UCC. Conclusions. The changes of morphological parameters, violated ratios of retinal layers and the neuroretinal architecture, which testify to a delayed physiological formation of the macula in children with UCC are among the main factors that limit the achievement of high visual functions after the surgery // Russian Ophthalmological Journal, 2016; 4: 16-21. doi: 10.21516/2072-0076-2016-9-4-16-21.